Congenital cytomegalovirus in Japan: More than 2 year follow up of infected newborns. Issue 1 (19th December 2017) - Koyano, Shin; Morioka, Ichiro; Oka, Akira; Moriuchi, Hiroyuki; Asano, Kimisato; Ito, Yushi; Yoshikawa, Tetsushi; Yamada, Hideto; Suzutani, Tatsuo; Inoue, Naoki
Abstract: Background: The aim of this study was to evaluate the outcome of congenital cytomegalovirus (CMV) infection identified on urine‐filter screening assay at >2 years' follow up, and to observe the clinical outcomes after anti‐CMV treatment. Methods: Sixty of 72 congenital CMV patients were enrolled and clinically observed for >2 years. Forty‐three were asymptomatic at birth; seven were symptomatic at birth but untreated with anti‐CMV drugs; and 10 were symptomatic and treated with anti‐CMV drugs. Results: Of the 43 asymptomatic patients, three developed hearing loss or language disability for which association with congenital CMV has been repeatedly reported, and two had neurological sequelae of which the etiology was unclear, indicating that the rate of CMV‐associated late‐onset sequelae was 7–12%. All seven symptomatic infants without treatment developed sequelae, while three of the 10 treated patients were free from any sequelae. Conclusions: The rate of late‐onset sequelae observed in Japan is similar to that reported in the USA and Europe. The treatment of symptomatic patients with antiviral agents results in favorable clinical outcomes. Thus, newborn urine–filter paper screening of congenital CMV infection is warranted.